Future strategies for phosphorus sustainability amid worsening global cycle imbalances - Wei Liu; Haijun Wang; Zhiwen Li; Tian Qin; Mingyang Li; Wuhu Guo; Yuejin Chen; Yanqi Liu; Evgeny Abakumov; Wenjuan Wang; Wending Huang; Xiaowen Ji; et al. (Proceedings of the National Academy of Sciences, 2026)
Global anthropogenic phosphorus (P) cycle changes require active management with differentiated sustainability strategies across countries. This study developed a universal framework that integrates the comprehensive P flow process with sustainability scenarios to assess global anthropogenic P flow patterns and explore future sustainability pathways and potential. The results indicated that the global P flow imbalance intensified from 1961 to 2022, with over 80% attributed to croplands. Crucially, global trade serves as a significant driving force, redistributing P resources and reinforcing the global complexity of P-pollution footprints, driven by 35 key countries. Our model projects that by 2050, individual measures like reducing fertilizer applications, improving feed conversion efficiency, and recycling organic fertilizers could save 50% of P and reduce P losses by 39%. Crop–livestock integration significantly improved P use efficiency, potentially extending the global phosphate rock extraction period by 400 ± 87 y (mean ± SD). However, due to the low baseline P use efficiency in cropping systems, P recovery from waste in developing countries remains limited, necessitating additional measures alongside the above high-leverage measures. These findings underscore the indispensable role of human consumption and the transformative potential of dietary shifts, which are essential given that no country can achieve significant P sustainability gains solely by reducing food waste or processing losses. Coordinated supply and demand-side measures linking cropping, livestock, and consumption offer key strategies and benefits for systematically and differentially advancing P sustainability at both global and national levels.